A Method of Improving Fiber-reinforced Composite Workpiece Surface Quality During the Machining on 5-axis CNC Machines. (2015) - Shchurov, I.A.
Abstract: Fiber-reinforced composite parts are often finally processed by machining. Complex-shaped surfaces are often cut using the CNC machines. The resulting composite workpiece surface quality is essentially dependent on angles between two vectors: the resultant cutting direction and he fiber direction. As 5-axis CNC machines support every imaginable tool movement it is reasonable to guide these movements so that the specified angles were the most favorable to obtain the best surface quality. The proposed method enables to secure the required tool movements. Computer software has been developed and a cutting simulation has been executed. The verification of the designed CNC-program with CAM systems has proven the efficiency of the method.